(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
The aim of this paper is to deeply analyse a very important and emerging topic: seized and confiscated enterprises and their management. Through a case study approach, researchers investigate ten Italian enterprises in traditional and non traditional mafias’ territories. These enterprises belong to different economic sectors and also have different dimensions. Based on the data that more than 80% of them end their own activities after the confiscation, the researchers try to understand what are endogenous and exogenous factors that allow to these enterprises to survive also in the legal markets. Keywords: Enterprises, seizure, confiscation, legislation, mafia organized crime